Adherence and barriers to HAART in Kiambu County, Kenya - Malek Bashti; Eduardo Palacios Fabre; Lars Osterberg (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Study design: We performed a cross-sectional study of HIV-positive patients from the Lusigetti Sub-County Hospital's Comprehensive Care Clinic (LCCC) to assess the adherence rate and potential barriers to Highly Active Antiretroviral Therapy (HAART).  Methods: Forty two percent of the clinic's adult patient population (102 of 243) was surveyed over the course of three months using the validated Simplified Medication Adherence Questionnaire (SMAQ), and ten additional questions (see appendix) to address barriers to adherence to HAART. Patient interviews were conducted in a private room, and responses to our survey were recorded without associated patient identifiers. Participation was voluntary, no incentives were provided to patients, and oral informed consent was obtained. Results: Fifty three percent (53 of 100) of patients were identified as adherent to HAART. Univariate logistic regression analysis revealed that the odds of adhering increased 2.8 fold with each level of greater perceived ease of access to medication refills (p= 0.0021).  Conclusions: This study suggests patient adherence to HAART in Lusigetti Sub-county Hospital is much lower than expected based on previous patient viral load tests. Among the barriers assessed, poor access to medication was the only statistically significant barrier to adherence. Since other countries in sub-Saharan Africa have similar processes for HIV medication refill and delivery, effective solutions for optimizing medication access could be implemented across other African nations in order to increase HAART adherence and improve the control of HIV.